The effect of rebranding on brand image and its impact on customer loyalty on Gojek - Firsan Nova (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine the effect of Rebranding on brand image and customer loyalty to Gojek. The data used are primary data from questionnaires distributed to 214 UNSADA student respondents who used Gojek services in the past year. The sample was taken using a non-probability sampling technique, the sampling method used purposive sampling, and the sample size was determined using the quota sampling method. Furthermore, the analysis was carried out using Structural Equation Modeling (SEM) and testing by LISREL. 8.8. based on the research results, there is a positive effect of Rebranding on customer loyalty through the brand image on Gojek. This is indicated by each t-value (t-values) which is 11.01 (rebranding to brand image), 5.20 (brand image to customer loyalty), 2.68 (rebranding to customer loyalty)> 1.96 (???? = 5%). As well as the test results of the influence of the intervening variable through the Sobel test, the value of t > 1.96 (???? = 5%) is 4.76. Based on these results, it can be said that brand image is a variable that has a positive influence or has a significant relationship.